Peningkatan Keterampilan Sosial bagi Siswa melalui Kegiatan Psikoedukasi - Nisaul Mahmudah; Bambang Nursiswanto; Doddy Hendro Wibowo (Universitas Kristen Satya Wacana Salatiga, 2022)
Online learning during the Covid-19 pandemic caused limitations in developing the affective aspect of students, namely social skills. The purpose of this psychoeducational activity is to improve social skills among peers in boarding school students at SMP Muhammadiyah Purwodadi. The form of service activities is carried out with a psychoeducational model. Psychoeducation services are provided to students in grades 7 and 8. The total number of students participating in the activity is 90 students. Psychoeducation activities carried out in the form of lectures, discussions, and questions and answers and supported by modern learning media can increase students understanding of how to improve social skills among students. Students hope that similar activities can be carried out again in the future.